Socio-economic effects and the value of open data: A case from Sweden - Tatjana Apanasevic (International Telecommunications Society (ITS), 2021)
Governmental and public organisations have historically been generating and accumulating vast amounts of data which could provide many potential benefits for society and national economies. One example of an important dataset is accounts payable providing information about purchases and expenditures of the governmental sector. Academic research in the area of open data is rather new and fragmented. There is a gap in understanding socio-economic impact of open government data ex post at organisational level. This research aims to understand what kind of socio-economic impact a municipality gains by publishing accounts payable as open data, and how municipalities perceive the major benefits, challenges and risks related to open publishing of this dataset. For analysis, we use the example of Swedish municipalities that are already publishing or preparing to publish accounts payable dataset as open data. We discuss costs related to open data initiative, and benefits related to open publishing of analysed dataset. We also provide more insights into benefits and challenges perceived by municipalities in relation to open publishing of accounts payable.
Keywords: 330; open data; open government data; municipality; socio-economic analysis; accounts payable